2022
DOI: 10.3389/fendo.2022.1004112
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for evaluation and analysis of difficulty in retroperitoneal laparoscopic adrenalectomy: A single-center study with prospective validation using LASSO-logistic regression

Abstract: BackgroundWhile it is known that inaccurate evaluation for retroperitoneal laparoscopic adrenalectomy (RPLA) can affect the surgical results of patients, no stable and effective prediction model for the procedure exists. In this study, we aimed to develop a computed tomography (CT) -based radiological-clinical prediction model for evaluating the surgical difficulty of RPLA.MethodData from 398 patients with adrenal tumors treated by RPLA in a single center from August 2014 to December 2020 were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Through the comprehensive comparison of different models, it was found that the RF model exhibits the best prediction performance, thus making it our recommended model. Furthermore, in comparison to clinical models in previous study ( 16 ), our RF model exhibited superiority as evidenced by 2000 Bootstrap tests (D = 7.155, P < 0.001). The discrimination power of models can be effectively compared using two measures: the Net Classification Index (NRI) and the Integrated Discrimination Improvement (IDI).…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Through the comprehensive comparison of different models, it was found that the RF model exhibits the best prediction performance, thus making it our recommended model. Furthermore, in comparison to clinical models in previous study ( 16 ), our RF model exhibited superiority as evidenced by 2000 Bootstrap tests (D = 7.155, P < 0.001). The discrimination power of models can be effectively compared using two measures: the Net Classification Index (NRI) and the Integrated Discrimination Improvement (IDI).…”
Section: Discussionmentioning
confidence: 47%
“…The final retained variables included “Shape Features” like “Maximum3DDiameter”. Moreover, many studies have generally confirmed that the maximum diameter of the tumor is an essential factor affecting the difficulty of removing AT ( 9 , 10 , 16 20 ). In addition, “First Order Features”, which are linearly correlated with the CT value of the tumor, such as “90Percentile” were also included.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations